ASME 2012 Summer Bioengineering Conference, Parts a and B 2012
DOI: 10.1115/sbc2012-80094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Severity of Rod Contour on Posterior Rod Failure in Setting of Lumbar Pedicle Subtraction Osteotomy (PSO): A Biomechanical Study

Abstract: Pedicle subtraction osteotomy (PSO) is a powerful technique to correct flat back deformity in the lumbar spine. Because corrections as great as 30–40 degrees can be achieved with this technique, contouring of the fusion rods can be quite extreme in PSO constructs. Rod failure (Figure 1) during the late post-operative period (<1 year) has been reported clinically and is commonly associated with pseudoarthrosis. In fact, instrumentation failure following PSO occurs frequently enough that several studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…The longer rods that span the entire length of the instrumented fusion are not connected to the screws at the osteotomy site, avoiding the need for severe angular bending, which may weaken the rod making it more vulnerable for early rod fracture (RF) and place the patient at greater risk of pseudarthrosis. [11][12][13][14] Smith et al [8][9][10] reported RF rates of 6.8% in 442 patients with adult spinal deformity (ASD), but noted RF rates as high as 15.8% in 114 ASD patients treated with PSO. Eighty-nine per cent of the patients who had RF had the failure at or adjacent to the PSO level and early RF occurred in 63% at a mean of 6.4 mo.…”
mentioning
confidence: 99%
“…The longer rods that span the entire length of the instrumented fusion are not connected to the screws at the osteotomy site, avoiding the need for severe angular bending, which may weaken the rod making it more vulnerable for early rod fracture (RF) and place the patient at greater risk of pseudarthrosis. [11][12][13][14] Smith et al [8][9][10] reported RF rates of 6.8% in 442 patients with adult spinal deformity (ASD), but noted RF rates as high as 15.8% in 114 ASD patients treated with PSO. Eighty-nine per cent of the patients who had RF had the failure at or adjacent to the PSO level and early RF occurred in 63% at a mean of 6.4 mo.…”
mentioning
confidence: 99%
“…Recent biomechanical reports indicate that rods contoured with a device such as a French bender, and those with extreme angular bends (eg, at a PSO site), display a significantly lower fatigue life [17,18]. In the case of a corrective osteotomy, the outrigger rod technique allows the placement of supplemental rods with less acute bends than the primary rods.…”
Section: Discussionmentioning
confidence: 98%
“…The two primary rods are cut to appropriate length and then carefully contoured to avoid stress-risers associated with sharp angular bends [18]. The rods are placed within the screw heads, and preliminary set-screw tightening is performed.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Tang and colleagues demonstrated that greater angular bending of rods, such as that occurring across a PSO, significantly reduced rod fatigue life. 85 This finding, in combination with the high rates of RFs across PSOs, has led many surgeons to use additional rods to span osteotomy levels. Multiple rod configurations have been described (Fig.…”
Section: Pseudarthrosis and Instrumentation Failurementioning
confidence: 99%